(untitled) (Bangladesh Journal of Zoology, 2019)
Two catfish: Clarias batrachus (Linnaeus) and C. gariepinus (Burchell) were selected for examination during June, 2014 to May, 2016. The percentage (g/100 g) of nutrients such as moisture, ash, fat, protein, carbohydrate contents (mg/100 g) and energy (K cal) in C. batrachus and C. gariepinus was determined. Analyses were done to measure the nutrition value of edible body parts (flesh) of C. batrachus and C. gariepinus. The effects of modifying factors such as, season, sex, length, and diet of the hosts on the abundance of parasites were also studied. Present observation on biochemical analysis showed small variation in nutrient contents between C. batrachus and C. gariepinus. Protein, fat, moisture, carbohydrate levels were higher in non-infected C. batrachus (moisture 78.25 ± 0.06 g/100 g, ash 1.42 ± 0.09 g/100 g, fat 1.20 ± 0.04 g/100 g, protein15.05 ± 0.19 g/100 g, carbohydrate 5.53%) and non-infected C. gariepinus (moisture 78.62 ± 0.01 g/100 g, ash 1.22 ± 0.10 g/100 g, fat 1.19 ± 0.03 g/100 g, protein 14.69 ± 0.07 g/100 g, carbohydrate 4.95% than those of infected C. batrachus and C. gariepinus. In both species the highest presence of most of the nutrient components was observed in winter. Bangladesh J. Zool. 47(1): 27-39, 2019